ANALYSIS STUDENTS' ENGAGEMENT THROUGH STORYTELLING IN SPEAKING ENGLISH - Zai, Peristiwa Diken Kasatria; Gulo, Ceria Putri Damai; Gulo, Dwi Kurnia; Zebua, Anes Mutiara Putri; Zebua, Novita Purnawirati (El-Fata: Jurnal Ilmu Tarbiyah, 2025)
Speaking skills in English are essential for students to communicate effectively in a global environment. However, many students struggle with speaking English due to a lack of engagement, confidence, and exposure to real-life communication situations. This study aims to analyze the impact of storytelling on students' engagement in speaking English and to identify the challenges they face when using this method. This research employs a qualitative approach, using observation, interviews, and questionnaires as data collection instruments. The participants are 24 eighth-grade students from SMP Negeri 1 Sitolu Ori, selected through purposive sampling. The findings reveal that storytelling enhances students' engagement in speaking English, boosts their confidence, and improves pronunciation and fluency. However, students face challenges such as difficulties in structuring stories, pronouncing complex words, and nervousness when speaking in front of the class. These findings indicate that storytelling can be an effective strategy for improving students' engagement in speaking English, but it needs to be supported by continuous practice and teacher guidance.